168 Supplementation of Organic and Inorganic Selenium on Oxidative Stress of Weaned Pigs. 2. Antioxidant Capacity. (10th April 2018) - Doan, N; Ji, P; Kim, K; Bravo, D; Liu, Y
Abstract: Several endogenous antioxidant enzymes are selenoproteins. Supplementing appropriate amount of selenium (Se ) in feed may contribute to neutralize cellular reactive oxygen species, therefore improving animal health and performance. We aimed to evaluate different sources of Se in mitigating diquat-induced oxidative stress in weaned pigs. Thirty-five pigs (9.72 ± 1.39 kg) were individually housed and randomly assigned to one of five treatments with 7 replicates per treatment. Five treatments included a negative control (NC ) and a positive control (PC ), in which pigs were fed a basal diet without or with diquat injection. The basal diet was not supplemented with any Se. Pigs in the other 3 treatments were fed with the diets supplemented with 0.3 mg/kg of Se from sodium selenite, Se yeast, or soybean protein chelated Se. The experiment lasted 17 days, including 10 days before and 7 days after diquat injection. In the PC and Se groups, all pigs were intraperitoneally injected with diquat at 10 mg/kg BW on day 11. Pigs in the NC group were intraperitoneally injected with sterile 0.9% saline. Pigs were weighed at d 0, 10, and 17 and daily feed allotments were recorded to calculate growth performance. Blood samples were collected at 0 h (prior to injection), and at 6 h, 24 h, 2 d, 4 d, and 7 d post-injection (PI ) to analyze complete blood counts, activities of glutathione peroxidase (GPx ), superoxide dismutase (SOD ), total antioxidant capacity (TAC ), and plasma malondialdehyde (MDA ). All data were analyzed using the PROC MIXED of SAS with a randomized complete block design and repeat measurement. Diquat injection increased ( P < 0.05) red blood cells on 6 h, 24 h, 2 d, and 7 d PI and enhanced ( P < 0.05) hemoglobin concentration at 24 h and 2 d PI. Diquat injection increased ( P < 0.05) plasma MDA at 6 h and 2 d PI but reduced ( P < 0.05) plasma GPx activity at 2 d and 7 d PI, indicating that the oxidative stress induced by diquat injection impairs the antioxidant capacity of weaned pigs. Supplementation of different types of Se reduced ( P < 0.05) plasma MDA and enhanced ( P < 0.05) plasma SOD and TAC at different time period, compared with the PC. In conclusion, dietary supplementation of any of 3 Se products at 0.3 mg/kg improved antioxidant capacity, therefore reduced oxidative stress of diquat challenged pigs.